Pemanfaatan Hidrolisat Talas (Colocasia esculenta L.) pada Kultur Miksotrofik Mikroalga Tetraselmis chui: Pengamatan Pertumbuhan dan Kadar Lipida - Mohamad Agus Salim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to observe the potential use of taro hydrolysate (Colocasia esculenta L.) as a source of complex organic carbon to produce optimum cell density, biomass, lipid and chlorophyll content from T. chui microalgae under myxotrophic conditions. The culture was carried out in a vial containing 400 mL of bold basal medium. Taro hydrolysate is given in five concentrations, namely: 0, 5, 10, 15 and 20 g/L. The results showed that T. chui microalgae could grow in myxotrophic conditions with the addition of taro hydrolysate in the concentration range of 5 to 20 g/L. The maximum cell density and dry weight in the addition of 10 g/L taro hydrolysate were 4.23 x 105 cells/ml and 0.57 g/L, respectively. Meanwhile, the maximum fresh weight and lipid content were achieved at the addition of 15 g/L taro hydrolysate, namely 4.85 g/L and 67.4%. Chlorophyll content decreased with increasing concentration of taro hydrolysate. In conclusion, the use of taro hydrolysate can increase cell density, fresh weight and dry weight, lipid content and decrease the chlorophyll content of T.chui microalgae in myxotrophic culture. Keywords: Taro Hydrolysate, Lipid, Mixotrophic, Growth, Tetraselmis chui